The subassociation Salici rosmarinifoliae-Betuletum borysthenicae typicum in the lower Dniper arenas (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
According to principles the J.Braun-Blanquet, plant communities are investigated with Betula borysthenica domination, which grow in lover Dniper arenas. The new association Salici rosmarinifoliae-Betuletum borysthenicae is recognized with giving diagnostic species, nomenclature type and brief information on ecology and distribution.
Keywords: syntaxonomy, vegetation, arenas of Dniper.